Estimation of Fluctuation Characterizations by USV-Operation Simulations in Sea State 3. (6th November 2017) - Park, Jae-Han; Bae, Ji-Hun; Baeg, Moon-Hong
Abstract : This paper proposes a method based on simulation techniques for fluctuation characterizations of unmanned surface vehicle (USV) operations under Sea State 3. In order to simulate the operations of a USV in Sea State 3, we generated the data of sea surfaces using linear wave theory and utilized the motion equation. Fluctuation analysis results by the proposed simulation method could provide crucial information for designing the stabilization system for the critical equipment on a USV. Through these works, it was verified that the design specifications such as range of motion, maximum speed, and acceleration could be estimated using the simulation data.